PELATIHAN PENGKLASIFIKASIAN PERSEDIAAN DI RUMAH SAKIT UMUM DAERAH KABUPATEN KARANGANYAR - Handayani Tri Wijayanti; Rima Parawati Bala (STIE Atma Bhakti, 2021)
ABSTRACTCommunity Service Activities are carried out at the Regional General Hospital (RSUD) Karanganyar Regency. Changes in the inventory classification presented in the 2020 financial statements due to the implementation of the Minister of Home Affairs Regulation Number 90 of 2020 became a problem for partners. This is because the partner's inventory expenditure budget still uses the old regulations based on the Minister of Home Affairs Regulation Number 64 of 2013, so partners must adjust and reclassify inventory records to be able to present details of their inventory and inventory expenditures in the financial statements in accordance with the new regulations. For this reason, partners need academic assistance in rearranging the standard chart of account for inventory and inventory spending, which is adjusted to the Minister of Home Affairs Regulation Number 90 of 2020. The purpose of this community service activity is to help partners compile a standard chart of accounts for inventory and inventory spending so that inventory transactions can be recorded. and reported consistently in the coming year based on the latest regulations. This activity was carried out in the form of training for two days on April 8 and 9, 2021. The results of this activity provided benefits for partners, namely in the form of a final draft of changes to the standard inventory chart of accounts and inventory spending as a guide in preparing inventory budgeting and presenting it in financial statements that are consolidated with the financial report of the Karanganyar District Health Office. Keywords: Standard Chart of Accounts, Inventory, Reclassification